Diagnósticos de enfermagem da classe : respostas cardiovasculares/pulmonares em clientes submetidos à cirurgia bariátrica - Moreira, Rosa Aparecida Nogueira (2012)
The bariatric surgery is included in the complexity of the treatment of obesity. Then, knowing the related factors and defining characteristics of cardiopulmonary diagnostic associated with the immediate postoperative period of bariatric surgery becomes essential for the development of nursing care, since, from the most prevalent nursing diagnoses, interventions will be instituted. Thus, the study aimed to evaluate the profile of nursing diagnosis of the class cardiovascular/pulmonary answers according to NANDA Taxonomy II of the patients after bariatric surgery. A cross-sectional study was conducted with 59 patients hospitalized in a referral hospital for bariatric surgery in the city of Fortaleza, state of Ceará, which data collection occurred from June 2010 to June 2011. Information was collected through interviews and physical examinations; then three judges made the inference of nursing diagnoses in the class cardiovascular/pulmonary answers according to the NANDA-I Taxonomy 2009-2011. The data were compiled in an Excel spreadsheet and the statistical analysis was carried out in the STATA version 8.0. The significance level in this study was 5%. There was a predominance of females, mean age of 35.3 years. Most patients had a diagnosis of morbid obesity with BMI>40kg/m2. The actual diagnoses of greater agreement among the judges were Ineffective Peripheral Tissue Perfusion (78%), Decreased Cardiac Output (76.3%), and Activity Intolerance and Ineffective Breathing Pattern (47.5%). Decreased peripheral pulses, edema, altered preload and afterload fatigue were proportionally associated with the diagnosis Decreased Cardiac Output. Changes in respiratory depth, dyspnoea, orthopnoea, use of accessory muscles for breathing, anxiety, pain, fatigue, respiratory muscle fatigue were proportionally associated with Ineffective Breathing Patterns. Discomfort in efforts, verbal report of fatigue, verbal report of weakness, abnormal blood pressure response to activity, sedentary lifestyle, immobility and bed rest were proportionally associated with Activity Intolerance. Edema, paresthesia, decreased pulses, hypertension and smoking were proportionally associated with Ineffective Peripheral Tissue Perfusion. This study will contribute to the construction of the Systematization of Nursing Care regarding nursing diagnoses of the class cardiovascular/pulmonary answers, as described in the results presented, and in the scientific basis for each diagnosis. Besides the important contribution to identifying the real needs and facilitating the use of appropriate interventions in this population, it is the ability of the professionals in taking advantage of this information, in view of the scarcity of researches related to nursing diagnoses in patients undergoing bariatric surgery.